2011
DOI: 10.1016/j.ejcts.2010.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Thymoma: inter-relationships among World Health Organization histology, Masaoka staging and myasthenia gravis and their independent prognostic significance: a single-centre experience

Abstract: In thymomas, MG, WHO histology and Masaoka stage are inter-related. MG has an influence on histology and stage at presentation, while two clinical/histologic patterns are more likely: early Masaoka stage A/AB WHO type and high Masaoka stage/B WHO type. Among the three factors, only Masaoka stage had a prognostic significance on OS and DFS. Our results suggest that a consistent staging system for thymomas should take into account all three variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 24 publications
5
62
1
Order By: Relevance
“…Other studies did not find differences in survival between type B3 thymoma or atypical thymoma and other thymomas 45,55 and failed to show an association of WHO or proposed Suster and Moran classification with outcome. 45,56,57 These varying results might have been, at least in part, due to interobserver variation. Indeed, studies reported an only fair to moderate reproducibility of the 2004 WHO classification of TET, with j values ranging between 0.39 and 0.53 or an overall concordance rate of 63% to 70%.…”
Section: Staging Is Prognostically Superior To Histomorphologic Classmentioning
confidence: 98%
“…Other studies did not find differences in survival between type B3 thymoma or atypical thymoma and other thymomas 45,55 and failed to show an association of WHO or proposed Suster and Moran classification with outcome. 45,56,57 These varying results might have been, at least in part, due to interobserver variation. Indeed, studies reported an only fair to moderate reproducibility of the 2004 WHO classification of TET, with j values ranging between 0.39 and 0.53 or an overall concordance rate of 63% to 70%.…”
Section: Staging Is Prognostically Superior To Histomorphologic Classmentioning
confidence: 98%
“…Staging is the most important prognostic factor. Age, gender, and other immunological diseases are not significant [2,[6][7][8][9][10]. In the current case, there was no recurrence after one year of postoperative follow-up.…”
Section: Discussionmentioning
confidence: 77%
“…However, this is not definitive as the patients with thymoma also had a trend for worse outcome with induction therapy (5-year OS 57% vs. 87%; P=0.084). These subgroup analyses involving stratification of specific factors don't account for all potential confounding factors, since there is a strong correlation between Masaoka-Koga stage and histologic subtype of TETs (33). A multivariate model adjusted for these factors may have assisted in estimating the true effect of induction therapy.…”
Section: Biopsy For Patients With An Anterior Mediastinal Mass and Mymentioning
confidence: 99%
“…In our opinion, the authors could more strongly conclude the importance of stage and "downstaging" since it was the only factor that had a clear impact on outcome. WHO histology may be a surrogate for stage and analyses adjusting for stage may eliminate the importance of WHO histology as a prognostic factor (33).…”
Section: The Importance Of 'Downstaging'mentioning
confidence: 99%